Light Micro and Ultrastructural Studies on the Coagulating Gland of Albino Rat (Rscopic and rattus Norvegicus) - Bindu, M.; Kishore, P. V. S.; Raju, N. K. B.; Nagamalleswari, Y.; Sreenu, Makkena (Indian Journal of Veterinary Anatomy, 2015)
The coagulating gland in the rat was compound tubular accessory sex gland. The parenchyma consisted of the secretory units and ducts lined by simple cuboidal or low columnar epithelium which formed folds inside the compartments. The secretory activity was merocrine and apocrine. Ultrastructural study revealed secretory cells of different electron density. These cells had oval nuclei with small nucleoli and the peripheral chromatin. In the cytoplasm, the endoplasmic reticulum was mostly located in the perinuclear area and was granular having studded with ribosomes. The mitochondria, smooth endoplasmic reticulum and the Golgi apparatus were also observed at various locations. The cytoplasm also contained the secretory granules and the vacuoles of different sizes towards the luminal side. The luminal surface had the surface microvilli.